Large-scale data streaming, processing, and blockchain security - Saini, Hemraj, 1977-; Rathee, Geetanjali, 1990-; Saini, Dinesh Kumar, 1974- (Advances in information security, privacy, and ethics (AISPE) book series., 2021)
"This book explores the latest methodologies, modeling, and simulations for coping with the generation and management of large-scale data in both scientific and individual applications"--